EFEKTIVITAS E-HUMAN DEVELOPMENT WORKER DALAM PENDATAAN DAN PENCEGAHAN STUNTING - Nadya Rizqiyah; Lailul Mursyidah (Journal Publicuho, 2025)
This study aims to analyse the effectiveness of the Electronic Human Development Worker (e-HDW) system in data collection and stunting prevention in Kupang Village, Jabon District, Sidoarjo Regency. The background of this research lies in the high rate of stunting in the area, requiring digital innovation for child nutrition monitoring and reporting. The study uses a qualitative approach with data collected through observation, interviews, and documentation involving village health cadres and public health centre staff. The analysis is based on Richard M. Steers’ organisational effectiveness theory, which includes three main indicators: goal attainment, integration, and adaptation. The results show that in terms of goal attainment, e-HDW improves data accuracy and accelerates early detection of stunting cases. In terms of integration, the system enhances inter-sectoral coordination among cadres, health centres, and local governments with adequate support and facilities. Regarding adaptation, cadres successfully adjust to digital systems through regular training and supervision. Based on these findings, it can be concluded that the implementation of e-HDW is effective in improving data management, strengthening collaboration, and accelerating stunting reduction efforts in Kupang Village.